Anesthesia management in a patient with anomalous origin of left pulmonary artery from the descending aorta: A case report and literature review - Wang, Lu; Li, Yaru; Yin, Xinrui; Han, Qiaoyu; Feng, Yi; Shi, Yi; Liu, Gang; Sun, Liang (Frontiers in Surgery, 2023)
Anomalous origin of the left pulmonary artery from the descending aorta is an extremely rare congenital malformation. There were merely four case reports of such malformation in the previous literature, and all four cases undergone surgery repair in their first year of life. Actually, long-term pulmonary arterial hypertension and irreversible pulmonary vascular changes make the anesthesia management pretty challenging, while anesthesia for managing these cases has not been discussed before. We present a 15-year-old boy undergoing corrective surgery and try to provide some tips on anesthesia management for this surgical procedure. Through optimal perioperative management, successful outcomes can be achieved for this disease.